Long noncoding RNA SNHG22 increases ZEB1 expression via competitive binding with microRNA-429 to promote the malignant development of papillary thyroid cancer. Issue 10 (18th May 2020) - Gao, Hong; Sun, Xiaosong; Wang, Hongdong; Zheng, Ying
ABSTRACT: Long noncoding RNA termed small nucleolar RNA host gene 22 (SNHG22) is a crucial regulator in epithelial ovarian carcinoma. Nevertheless, the regulatory functions of SNHG22 in papillary thyroid cancer (PTC) progression and its mechanisms of action remain poorly defined. Therefore, the present study aimed to investigate the role of SNHG22 in the malignant phenotype of PTC and determine whether SNHG22 regulates PTC progression via a ceRNA mechanism. SNHG22 expression in PTC was detected using reverse transcription–quantitative polymerase chain reaction analysis. The biological actions of SNHG22 silencing in PTC cells were evaluated both in vitro (using Cell Counting Kit-8 assay, flow cytometry analysis, and cell migration and invasion assays) and in vivo (using tumorigenicity assay). Herein, high SNHG22 expression was observed in PTC tissues and cell lines. This high SNHG22 level was closely associated with unfavorable clinicopathological characteristics and worse overall survival in patients with PTC. SNHG22 knockdown effectively suppressed PTC cell proliferation, migration, and invasion in vitro; accelerated cell apoptosis; and hindered tumor growth in vivo. Mechanistic experiments revealed that SNHG22 directly interacts with microRNA-429 (miR-429) as an miRNA sponge and positively modulates ZEB1 expression. Rescue assays found that miR-429 inhibition or ZEB1 upregulation can offset the actions of SNHG22 knockdown in PTC cells. In sum, SNHG22, miR-429, and ZEB1 form an interactive regulatory network with cancer-promoting roles in PTC cells, suggesting that the SNHG22/miR-429/ZEB1 pathway is a novel diagnostic and therapeutic target.